2005
DOI: 10.1086/431227
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Silicate Emission from Quasars at 10 and 18 Microns

Abstract: We report the spectroscopic detection of silicate emission at 10 and 18 mm in five PG quasars, the first detection of these two features in galaxies outside the Local Group. This finding is consistent with the unification model for active galactic nuclei (AGNs), which predicts that an AGN torus seen pole-on should show a silicate emission feature in the mid-infrared. The strengths of the detected silicate emission features range from 0.12 to 1.25 times the continuum at 10 mm and from 0.20 to 0.79 times the con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
223
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(248 citation statements)
references
References 29 publications
23
223
1
1
Order By: Relevance
“…Fig. 1 in Hao et al 2005). The measurement on 2007 Feb. 07 has a relatively steep, increasing spectrum and flux values consistent with the Spitzer spectrum at the long wavelength end.…”
Section: C 273supporting
confidence: 68%
See 2 more Smart Citations
“…Fig. 1 in Hao et al 2005). The measurement on 2007 Feb. 07 has a relatively steep, increasing spectrum and flux values consistent with the Spitzer spectrum at the long wavelength end.…”
Section: C 273supporting
confidence: 68%
“…5 from 2007 Feb. 28 and 2007 Jun. 28 as well as the spectrum in Hao et al 2005Hao et al from 2004 Jan. 06) show variations of less than 10% and are also consistent with the VISIR and TIMMI2 photometries. Hence we see no evidence for any significant variability during our observations.…”
Section: C 273supporting
confidence: 67%
See 1 more Smart Citation
“…For a silicate temperature of 260 K -consistent with the range found for other quasars (e.g. Hao et al 2005) -the simulated spectrum reproduces the observed strengths of the 9.7 and 18 μm features.…”
Section: Silicate Emissionsupporting
confidence: 83%
“…For type 1 AGN, the situation is less clear. Early reports of the silicate emission feature in a number of quasars discussed that the central wavelength might be shifted towards longer wavelengths (Hao et al 2005;Siebenmorgen et al 2005;Sturm et al 2005). Recently Nikutta et al (2009) suggested that radiative transfer effects might cause the silicate emission feature in AGN to shift towards longer wavelengths.…”
Section: The N-band Silicate Feature In Agn At High Spatial Resolutionmentioning
confidence: 99%